A novel 2-cyanobenzothiazole-based 18F prosthetic group for conjugation to 1, 2-aminothiol-bearing targeting vectors1. Issue 12 (28th March 2015) - Inkster, James A. H.; Colin, Didier J.; Seimbille, Yann
<x xml:space="preserve">Abstract</x> [18F]FPyPEGCBT is a new 18F labelling agent which contains a 2-substituted pyridine for incorporation of [18F]F− and a 2-cyanobenzothiazole moiety for chemo-selective conjugation to 1, 2-aminothiol-bearing biomolecules.